Research topic modeling in informatics engineering study program at Nusa Putra University using LDA method - Kamdan; Ivana Lucia Kharisma; Gina Purnama Insany; Paikun (Nusa Putra University, 2022)
Writing research reports at the undergraduate level is one of the obligations that must be fulfilled by students as a fulfillment of graduation requirements at a university. One of the independent learning programs implemented at Nusa Putra University is through the research method, where students are required to conduct research as a graduation requirement in the Study Completion Program course. The growing development of information and communication technology provides opportunities for students to determine research themes. However, sometimes students take research themes that are not in accordance with the concentration in the study program. This research was conducted with the aim of identifying how the LDA topic modeling method can analyze research topic trends by modeling topics on research titles that have been taken by students at the Informatics Engineering Study Program, University of Nusa Putra. Latent Dirichlet Allocation (LDA) is one of the most popular topic modeling methods today. This research uses a dataset in the form of 159 titles of study completion program research reports and tittles of final assignment reports for students of the Informatics Engineering study program, University of Nusa Putra. This research is expected to be a reference in conducting research by students based on the topics that have been modeled